(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
In this paper, we present a literature review based on articles in journals dealing with teacher education in dialogue with decoloniality, in order to investigate the context of the research carried out. We observe that the works have a wide spectrum of discussions, in a movement of resistance and re-existence to transform pedagogical practices. They involve subjects (teachers, students, communities) in different contexts: indigenous education, ethnic-racial relations, gender and sexuality issues, refugees and others. The most cited authors are Catherine Walsh, Walter Mignolo, Anibal Quijano, Paulo Freire, and Vera Candau. The school is a space where colonialities are reproduced, therefore, the importance of expanding the dialogue with teachers is perceived, so that, in addition to specific knowledge, they meed to discuss social, political, economic, environmental, in a decolonial perspective. There are few works in the field of science and mathematics education.